Carer's perception of and reaction to reassurance seeking in obsessive compulsive disorder. (17th August 2017) - Kobori, Osamu; Salkovskis, Paul M.; Pagdin, Rowena; Read, Julie; Halldorsson, Brynjar
Abstract: The purpose of the present study was to explore the experience of being asked for reassurance from the perspective of carers of obsessive compulsive disorder (OCD) sufferers, and to examine its relationship to sufferers' reassurance seeking by a direct comparison with data obtained from the person they normally offer reassurance to. Forty-two individuals with OCD and their carers completed alternate versions of the Reassurance Seeking Questionnaire. Result suggest that carers report most commonly providing reassurance when asked to do so, and the frequency of their reassurance provision is associated with how carefully sufferers seek reassurance, rather than their OCD symptom severity. The carer's perspectives on the impact of reassurance provision was accurate; both sufferers and carers perceive that reassurance works only temporarily, but even if the anxiety-relieving effect of reassurance decreases in the medium term, it is likely to be perceived as beneficial because carers accurately perceived that sufferers would feel much worse if they refused to provide reassurance. The present study is the first to quantitatively investigate carer's experiences of reassurance provision, and elucidate why carers feel the need to provide it.